Developing a strawberry lexicon to describe cultivars at two maturation stages. Issue 1 (22nd January 2018) - Oliver, Penelope; Cicerale, Sara; Pang, Edwin; Keast, Russell
Abstract: The sensory profile of strawberries is documented as being influenced by cultivar, maturation stage, and environment. Thus, internationally bred strawberries grown in Australia will have a flavor profile adapted to the Australian environment. The objective of this research was to devise a strawberry lexicon relevant to the sensory characteristics of commercially available strawberries grown in Australia. A quantitative descriptive analysis (QDA) trained panel developed a lexicon consisting of two appearance, eight aroma, ten flavor, and five textural/mouthfeel attributes to describe the strawberries. The panel subsequently applied the developed lexicon to describe the sensory attributes of six strawberry cultivars of two flowering types, grown in Australia and harvested at two different maturation stages. A principal component analysis (PCA) determined three dimensions of which the attributes explained 86% of the variance. There were significant differences identified between strawberries, attributable to flowering type, cultivar and maturation stage, validating the developed lexicon to discriminate strawberries. Practical applications: Strawberries are a commonly consumed berry, with an abundance of cultivars grown worldwide. The sensory profile of strawberries is dependent upon the cultivar and environmental conditions of which the strawberry is grown. This research has identified differences attributable to maturation stage, cultivar, and flowering type. Therefore, the development of a sensory lexicon via this research, applicable to the environmental conditions where cultivars are grown, will assist ongoing breeding programs in developing strawberries expressing flavors shown to be associated with liking.